A case study in the acquisition of three types of morphemes in English by a bilingual child - Quesada Pacheco, Allen (Universidad de Costa Rica, 2016)
This case study looks closely at the bilingual first language acquisition of a Costa Rican child who was raised through OPOL (One Parent One Language) and Minority Language at Home (mL@H).The subject, Itzel, was raised in a Spanish-speaking environment and her dad is the only person that has spoken to her in English since her birth up to the present. It is explained throughout the study that the use of several native English resources complemented the acquisition of the English language. For this study, a descriptive method was used. The Wug test was applied to the subject to determine the level of acquisition of the plural morphemes, third person singular morphemes, and past tense morphemes of regular verbs. Finally a comparison of 2011 Wug test and 2014 test is made to determine mastery of these morphemes in a period of three (3) years. The results proved that the subject did acquire naturally the studied morphemes and the Wug test shows some aspects of the interlanguage development related to the acquisition of morphemes done by the subject of the study.